Vibration signal for identification of concrete drilling process and drill bit wear. (January 2020) - Lazarová, Edita; Kruľáková, Mária; Labaš, Milan; Ivaničová, Lucia; Feriančiková, Katarína
Highlights: Experimental drilling rig with automated control and monitoring system was used. Vibration signal generated in various drilling regimes was analyzed in time domain. Information on applied regime change is carried by vibrations in drilling course. Information on drill bit condition is carried by vibrations in horizontal plane. Vibration signal may be used for optimization of maximum drill bit lifetime. Abstract: The use of vibration signal as a diagnostic parameter of the drilling process appears to be a potentially successful approach. The purpose of the research was to identify correlation between applied regime and vibrations, between specific energy and vibrations, and to identify wear of drilling tool on the basis of the vibrations. We observed that the acceleration of vibrations is the carrier of the information on the change of the applied regime. The curves of values of the specific energy and the reciprocal values of the vibration acceleration in the drilling axis have the same tendency. When the selected drilling regime is inappropriate, the values of the specific energy, vibration acceleration, and the tool wear intensity increase. The vibration acceleration limit values were determined, corresponding to the minimum values of the specific energy; they create the preconditions for the use of the vibrations in online systems for the optimal control.